2020
DOI: 10.3390/ijms21197423
|View full text |Cite
|
Sign up to set email alerts
|

Wheat and Barley: Acclimatization to Abiotic and Biotic Stress

Abstract: Twelve articles (ten research papers and two reviews) included in the Special Issue entitled “Wheat and Barley: Acclimatization to Abiotic and Biotic Stress” are summed up here to present the latest research on the molecular background of adaptation to environmental stresses in two cereal species. Crucial research results were presented and discussed, as they may be of importance in breeding aimed at increasing wheat and barley tolerance to abiotic and biotic stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Wheat is one of the most important cereals [ 1 ]. Its applications are very diverse, ranging from food ingredients to feeds; additionally, due to its high adaptive capability, wheat is in cultivation worldwide [ 2 ] with several varieties selected recently or very ancient [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the most important cereals [ 1 ]. Its applications are very diverse, ranging from food ingredients to feeds; additionally, due to its high adaptive capability, wheat is in cultivation worldwide [ 2 ] with several varieties selected recently or very ancient [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is a major staple crop for several countries, grown on around 10 million ha in Africa and it comes from a type of grass ( T. aestivum L.) that is grown in countless varieties worldwide. As a result of a growing population, changing food preferences, and socioeconomic change associated with urbanization and industrialization, wheat consumption steadily increased during the past two decades in all African countries [ 30 , 31 ]. Wheat consumption provides up to 50% of daily calories and proteins.…”
Section: Cereal Cropsmentioning
confidence: 99%
“…Still, no other role has been investigated or reported for these genes in Arabidopsis or other crop plants. Hexaploid wheat, an important crop around the globe and its productivity, can be affected when exposed to abiotic stress [ 27 ]. In the current study, we have identified two functionally active VIH genes from hexaploid wheat ( Triticum aestivum L.), capable of utilizing InsP 7 as a substrate to generate InsP 8 .…”
Section: Introductionmentioning
confidence: 99%